2021
DOI: 10.3390/s21217389
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality-Based Therapy Improves Fatigue, Impact, and Quality of Life in Patients with Multiple Sclerosis. A Systematic Review with a Meta-Analysis

Abstract: Patients with multiple sclerosis (PwMS) have a high level of fatigue and a reduced quality of life (QoL) due to the impact of multiple sclerosis (MS). Virtual reality-based therapy (VRBT) is being used to reduce disability in PwMS. The aim of this study was to assess the effect of VRBT on fatigue, the impact of MS, and QoL in PwMS. Methods: A systematic review with meta-analysis was conducted through a bibliographic search on PubMed, Scopus, Web of Science, and PEDro up to April 2021. We included randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 84 publications
2
21
1
1
Order By: Relevance
“…Two of the included studies found statistically significant effects of VR on cancer-related fatigue. This is consistent with the previous literature, which found VRR effective for the treatment of chronic fatigue in other conditions, such as multiple sclerosis [60]. Regarding specifically cancer-related fatigue, however, the previous studies have focused on testing the effects of VR on acute cancer fatigue, for example during procedures such as chemotherapy infusions.…”
Section: Discussionsupporting
confidence: 91%
“…Two of the included studies found statistically significant effects of VR on cancer-related fatigue. This is consistent with the previous literature, which found VRR effective for the treatment of chronic fatigue in other conditions, such as multiple sclerosis [60]. Regarding specifically cancer-related fatigue, however, the previous studies have focused on testing the effects of VR on acute cancer fatigue, for example during procedures such as chemotherapy infusions.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, dyspnea activates a network of sensorimotor, cerebellar, limbic, and emotion-related areas (30). Exercise with VR systems is often used in neurorehabilitation therapies (patients with multiple sclerosis) and can lead to reduced levels of fatigue (31). In addition, exercising in a VR environment can lead to reduced feelings of pain and fatigue, such as in patients with spinal cord injury, compared with exercising in a no-VR environment (32).…”
Section: Discussionmentioning
confidence: 99%
“…A series of recent reviews which summarized the results of the studies carried out in the last 15 years, pointed out that VR-based training has a positive effect in PwMS as regards fatigue, quality of life and postural control, at least equal to, or greater than, conventional exercise (Cortés-Pérez et al, 2021;Nascimiento et al, 2021). However, it is noteworthy that most of the screened interventions targeted balance, gait or other lower limb function outcomes, while the use of this approach to improve UL function appears to have been explored less.…”
Section: Introductionmentioning
confidence: 99%